The Campus Teaching Program in Improving the Morals of Elementary School Students in Islamic Religious Education Subjects - Rahmat, Azwar; Ansyah, Edi; Salamah, Salamah; Purwaningatmaja, Yesi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This research aims to improve the moral values of fifth-grade students in the Islamic Religious Education subject at State Elementary School 24 Seluma through the Kampus Mengajar program. The method used is Classroom Action Research (CAR) following the Kemmis and McTaggart model, which includes planning, action, observation, and reflection stages. The object of this research is student morale, with 27 fifth-grade students as the research subjects. The research data consists of moral attitudes, specifically in the aspects of expressing gratitude and requesting help, sourced from student activities during the learning process. Data collection techniques included direct observation using observation sheets to measure the development of individual student behavior. Data analysis in this study employs comparative descriptive techniques and critical analysis. Quantitative data from observation sheets are calculated using average scores and percentages to track improvement trends in student morale from pre-cycle through Cycle II. Meanwhile, qualitative data from field notes are processed through data reduction and display to illustrate specific behavioral changes in expressing gratitude and requesting assistance. The action is deemed successful when the students' average moral score reaches the predetermined performance indicator of at least 75. The results indicate that the implementation of the Kampus Mengajar program successfully improved student morale gradually in each cycle. In Cycle II, the lowest score was 75, the highest was 96, and the average was 86. These findings indicate that the success criteria have been met and the program is effective in shaping the character and morale of elementary school students.